2006
DOI: 10.1002/anie.200503599
|View full text |Cite
|
Sign up to set email alerts
|

Tetraarylphosphonium Salts as Solubility‐Control Groups: Phosphonium‐Supported Triphenylphosphine and Azodicarboxylate Reagents

Abstract: Tremendous effort has been invested over the last few decades to develop novel supports to facilitate organic synthesis. These supports have been used not only to carry out multistep syntheses, [1] but also to bind catalysts, reagents,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 82 publications
(11 reference statements)
0
32
0
Order By: Relevance
“…The process was devised starting from commercially available 1,3-dibromobenzene which was converted into the key precursor e 3-(bromophenyl)diphenylphosphine sulfide via monophosphorylation with Ph 2 PCl followed by in situ addition of elemental sulfur to the corresponding phosphine (Scheme 2) [12]. The sequential treatment of monothiophosphorylated bromide with n-BuLi and N-vinyl pyrrolidone, N-(diethoxymethyl)valerolactam or N-vinyl caprolactam led to the formation of the target ligands with five-, six-, and seven-membered azacycloalkene moiety, isolated as viscous yellowish oils in moderate yields (38e61%) after chromatography purification.…”
Section: Synthesis Of Ligands and Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The process was devised starting from commercially available 1,3-dibromobenzene which was converted into the key precursor e 3-(bromophenyl)diphenylphosphine sulfide via monophosphorylation with Ph 2 PCl followed by in situ addition of elemental sulfur to the corresponding phosphine (Scheme 2) [12]. The sequential treatment of monothiophosphorylated bromide with n-BuLi and N-vinyl pyrrolidone, N-(diethoxymethyl)valerolactam or N-vinyl caprolactam led to the formation of the target ligands with five-, six-, and seven-membered azacycloalkene moiety, isolated as viscous yellowish oils in moderate yields (38e61%) after chromatography purification.…”
Section: Synthesis Of Ligands and Complexesmentioning
confidence: 99%
“…To a solution of (3-bromophenyl)diphenylphosphine, prepared according to the literature procedure [12] from 1,3-dibromobenzene (5.4 g, 23 mmol), n-BuLi (1.6 M in hexane, 15 mL, 24 mmol), and Ph 2 PCl (4. 8 g, 22 mmol), in 30 mL of THF at À50 C, sulfur (0.…”
Section: Synthesis Of (3-bromophenyl)(diphenyl)phosphine Sulfidementioning
confidence: 99%
“…[10,11] Recently, we reported that the tetraarylphosphonium (TAP) unit can be used as a solubility control group to modify and predict the solubility properties of supported reagents and synthetic intermediates. A number of TAP-supported reagents derived from triphenylphosphine, diethyl azodicarboxylate, [12] tributyltin chloride, [13] and dialkylcarbodiimide [14] have been prepared and successfully used in various reactions. Furthermore, the reagents by-products can be removed from the reaction medium by a precipitation/ filtration sequence.…”
Section: Introductionmentioning
confidence: 99%
“…These modifications of the original oxidant or reductant are considered to intend a separation-free or separation-friendly process. 4,5 Formation of triphenylphosphane oxide is practically insignificant matter in the separation process due to its facile crystallization in non-polar solvents. In contrast, separation of the other co-product, diethyl or diisopropyl hydrazinedicarboxylate requires highly capable column chromatography to isolate a target compound.…”
mentioning
confidence: 99%